Determinants Encouraging Tourists to Use Public Transport in Their Vacation Destination - Thomas Bausch; Alessandro~M. Peluso; Bartosz Bursa; Markus Mailer; Mercy~Lorlonyo Amegah (International Journal of Tourism Research, 2024)
Implementing the concept of sustainability in tourism needs a significant reduction of vacationists' ecological footprint at destination level. A key aspect there is tourists' travel mode choice on-site. Based on an online-panel based survey in Italy and Germany and applying ordinal regression, this study analyzes for the destination South Tyrol, the impact of five blocks of potential factors on public transportation (PT) usage during a vacation: sociodemographics, everyday mobility at residence, attitudes toward climate change and environment, preferences for cars, and PT services at the destination, including the availability of a guest card for free PT use. The results of an ordinal regression analysis show that the availability of a guest card and the level of daily use of PT at home significantly increase PT usage. This is countered by daily use of the car at home and a positive affinity toward cars, having a negative effect on PT use.
Keywords: 330; daily mobility; guest card; mobility habits; mode choice; public transportation; sustainable tourism mobility